A STUDY OF IQ, EQ, AND SQ AMONG SECONDARY SCHOOL STUDENTS IN KRISHNA DISTRICT (International Journal of Food and Nutritional Sciences, 2021)
This study investigates the levels of Intelligence Quotient (IQ), Emotional Quotient (EQ), and Spiritual Quotient (SQ) among high school students in Krishna District, Andhra Pradesh. The research also explores variations in these domains based on gender, school type (Government/Private), and locality (Rural/Urban). A sample of 600 students was selected using stratified random sampling.